2015
DOI: 10.5424/fs/2015242-05742
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Individual Tree Competition on Diameter Growth of Silver Birch in Estonia

Abstract: Aim of study: The present study evaluates a set of competition indices including spatially explicit indices combined with different competitor selection approaches and non-spatially explicit competition indices. The aim was to quantify and describe the neighbouring effects on the tree diameter growth of silver birch trees.Area of study: Region throughout Estonia. Material and methods:Data from the Estonian Network of Forest Research Plots was used. After quantifying the selected indices, the best non-spatial i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
34
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(39 citation statements)
references
References 53 publications
3
34
0
2
Order By: Relevance
“…Our results concerning the thresholds of uniform angel index under complete spatial randomness in different structure units also provided evidence to apply it with other numbers of neighbors instead of four neighbors. Several studies showed that appropriate selection of potential neighboring competitors of a subject tree depended on the radius of influence zone (Pukkala & Kolström, 1987) and different selection approaches (Aakala et al, 2013;Maleki et al, 2015) have been used among competition indices. However, our results showed that the influence of structure unit size on mingling and dominance structural indices depended on tree species and size spatial arrangement patterns to a great extent.…”
Section: Discussionmentioning
confidence: 99%
“…Our results concerning the thresholds of uniform angel index under complete spatial randomness in different structure units also provided evidence to apply it with other numbers of neighbors instead of four neighbors. Several studies showed that appropriate selection of potential neighboring competitors of a subject tree depended on the radius of influence zone (Pukkala & Kolström, 1987) and different selection approaches (Aakala et al, 2013;Maleki et al, 2015) have been used among competition indices. However, our results showed that the influence of structure unit size on mingling and dominance structural indices depended on tree species and size spatial arrangement patterns to a great extent.…”
Section: Discussionmentioning
confidence: 99%
“…It was desirable to keep the total sample size of subject and competing trees manageable by using a BAF AC ≥ 3. One recent investigation arrived at the conclusion that the Bitterlich angle count method was not the best method for selecting competitor trees [6]. Here, we contend that Bitterlich method should not be used exclusively for just selecting competitor trees, but rather the point sampling expansion factors should also be employed to scaling the competition indices up to a per ha level.…”
Section: Discussionmentioning
confidence: 99%
“…The BAF V estimator also has desirable features, such as additivity and efficiency, when used for estimating change with permanent plots. The general consensus of the literature suggests that the Grosenbaugh growth estimator, Equation (7), is more efficient than the additive estimator, Equation (6), for most forest conditions and remeasurement intervals [25,31,32]. The drawback of the Grosenbaugh estimator is that it is non-additive (incompatible), so that volume (V 2 = [V 1 + ∆V]).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the concept of the influencezone (Staebler 1951) we assumed an imaginary circle in which the center is defined by a tree, and its radius is 40% of the average height of trees in the first storey on each plot , Maleki et al 2015. In order to avoid biased estimations due to the interference from immediate non-measured neighboring trees outside the plot boundary, we established a boundary strip (buffer zone) inside the monitoring plot with a width equal to the radius of the influence zone.…”
Section: Predictors Of Tree Mortalitymentioning
confidence: 99%